2015
DOI: 10.1002/smj.2406
|View full text |Cite
|
Sign up to set email alerts
|

Resolving a dilemma of signaling bankrupt‐firm emergence: A dynamic integrative view

Abstract: Research summary: Predicting the emergence of bankrupt firms relying on firm signals involves a stigma-related dilemma. On the one hand, bankrupt firms tend to send positive signals through restructuring to decouple themselves from the stigma of bankruptcy. On the other hand, the preexistence of the bankruptcy stigma may reduce the signaling effectiveness of firms' restructuring efforts, making the outcome prediction difficult. We address this dilemma by developing a dynamic integrative view to extend signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 68 publications
(79 reference statements)
0
22
0
6
Order By: Relevance
“…Importantly, as prior research suggests, exits can be an important foundation for strategic renewal (Ren, Hu, & Cui, 2019), as they free up committed resources and, therefore, contribute to the formation of new ventures (Carnahan, 2017). Therefore, although exits are not costless (Moulton & Thomas, 1993) and potentially leave a stigma of -business failure‖ (Xia, Dawley, Jiang, Ma, & Boal, 2016), such responses may not necessarily be the end of the road.…”
Section: Accepted Articlementioning
confidence: 99%
“…Importantly, as prior research suggests, exits can be an important foundation for strategic renewal (Ren, Hu, & Cui, 2019), as they free up committed resources and, therefore, contribute to the formation of new ventures (Carnahan, 2017). Therefore, although exits are not costless (Moulton & Thomas, 1993) and potentially leave a stigma of -business failure‖ (Xia, Dawley, Jiang, Ma, & Boal, 2016), such responses may not necessarily be the end of the road.…”
Section: Accepted Articlementioning
confidence: 99%
“…Despite these attempts to survive bankruptcy proceedings, many Chapter 11 firms fail to reemerge from the reorganization process (Hotchkiss, John, Mooradian, & Thorburn, 2008). Although higher‐quality firms are generally thought to be more likely to emerge (Daily, 1994; Lee, Peng, & Barney, 2007; Xia et al., 2016), the outcomes of bankruptcy proceedings are difficult to predict. That is because the firm quality is not readily observable by outsiders due to the significant information asymmetry, which is further exacerbated by financial distress (Evans et al., 2014; Kahl, 2002; Mooradian, 1994).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…More than 7,000 bankruptcy cases are filed annually under Chapter 11 of the US Bankruptcy Code for reorganization, with hundreds of thousands additional cases filed around the globe (Gerdano & Flynn, 2018; Xia, Dawley, Jiang, Ma, & Boal, 2016). Whether a firm can reemerge from bankruptcy proceedings can significantly impact various stakeholder groups (Altman, 1984; Cremers, Nair, & Peyer, 2008; Trahms, Ndofor, & Sirmon, 2013), including employees (Alaka, 2006; Bae, Kang, & Wang, 2011; Graham, Kim, Li, & Qiu, 2015; Ponoroff, 1994), suppliers (Benerjee, Dasgupta, & Kim, 2008; Boone & Ivanov, 2012; Brown, Fee, & Thomas, 2009; Chu, 2012), customers (Hortaçsu, Matvos, Syverson, & Venkataraman, 2013; Kale & Shahrur, 2007; Kale, Meneghetti, & Shahrur, 2013; Lian, 2017), business partners (Boone & Ivanov, 2012), and local communities (Alaka, 2006; Bae et al., 2011; Graham et al., 2015; Ponoroff, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…We faced the problem of missing data [34,36,37], especially with respect to firm financial data and Research & Development (R&D) expenditures. Our sample was further reduced because we used lagged values (t-1) for all our independent variables [38][39][40], as prior research has shown, that capital markets usually need some time to incorporate the available firm information [41,42]. Hence, our final sample comprised 1,203 firm-year observations.…”
Section: Sample and Proceduresmentioning
confidence: 99%